Hoaks dan disinformasi politik sebagai ancaman terhadap kualitas demokrasi di indonesia: analisis dalam konteks pemilu - Arya, Afifah Bunga (Maliki Interdisciplinary Journal, 2026)
Hoaxes and political disinformation on social media have become a serious threat in maintaining the quality of democracy in Indonesia, especially in the implementation of elections. This study aims to analyze how the pattern of hoaxes and political disinformation spread, as well as their impact on society and on elections. The results of the study explained that the spread of hoaxes is structured and involves political actors, influencers and buzzers who use social media algorithms. The low digital literacy of the community is the main door for the spread of hoaxes to run smoothly. The impact of the spread of hoaxes and disinformation can reduce the quality of public trust in the government and cause horizontal conflicts between groups. Countermeasures have been regulated through the ITE Law, supervision by the Bawaslu and KPU institutions and education from educational institutions about digital literacy.